The rush for the North Pole: A furious start to Russia's Arctic Council chairmanship - Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2021)
Russia assumed the Chairmanship of the Arctic Council at the 12th Ministerial in Reykjavik, on 20 May 2021. Russian Foreign Minister Sergey Lavrov described his first meeting with US Secretary of State Antony Blinken the previous day as 'constructive'. Two days before the meeting, however, Lavrov warned the West against encroaching in the Arctic: 'It has been absolutely clear for everyone for a long time that this is our territory.' But what exactly did he mean? The polar region claimed by Russia in its March 2021 submission to the Commission on the Limits of the Continental Shelf? Or the ongoing disputes over the Northern Sea Route? Moscow is working to fortify its positions in the Arctic through a combination of aggressive rhetoric and offers of dialogue, in another example of its ambivalent policy mix of security and cooperation.
Keywords: 320